PERSEPSI MENGENAI MULTIFUNGSI LAHAN SAWAH DAN IMPLIKASINYA TERHADAP ALIH FUNGSI KE PENGGUNAAN NON PERTANIAN - RAHMANTO, BAMBANG; IRAWAN, BAMBANG; KHOIRIYAH AGUSTIN, NUR (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 6, No. 2 Juli 2006, 2012)
Phenomena of paddy field conversion to non agricultural purposes has been worried, especially conversion in Java. Paddy fields have multi functions that related to many aspects, such as economic, socio-cultural, ecological environment, amenity, and national food security. Massive conversion of paddy field will caused externalities. Inadequate appraisal of Paddy field multi functions become one of determinant factors for speeding up process of paddy field conversion. Outcome of this research indicate that both village society and regional development stake holder give less appreciation to other elements of Paddy field multi functions rather than its capacity as food stock and labor absorption. Farmers Appreciation for its function as environmental conservation and intrinsic values of paddy field are varied. Farmers aged, education, and the wide of land cultivation tend to affect positively. Meanwhile, the differences of region characteristic tend to affect the differences of farmers opinion in causal factor of environmental degradation.
Keywords: Perception, Multi Functions, Conversion, Paddy Fields.